2011
DOI: 10.1111/j.1365-2109.2011.02948.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of nutrient from fish food and effects on Microcystis aeruginosa growth

Abstract: This study aimed to explore the relationship between Microcystis aeruginosa growth and nutrients released from fish food, which mainly simulates the effect of uneaten food on algae growth and water quality variables during aquaculture activities. Fish food (0, 0.1, 0.2, 0.5 and 1 g dosages tested) of different grain sizes (original; 0.147 ≤ d ≤ 0.85 mm; d ≤ 0.147 mm) was added each into M‐II culturing medium (nitrogen and phosphorus absent). During the experimental running period, the concentrations of total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…In addition, aquaculture activities not only stimulate algal growth but also affect phytoplankton communities 40,41 along with deteriorating water quality and adversely influencing human health aquaculture activities 42 . Wu et al 's results showed that the release of N and P from fish feed stimulated algae growth 43 . Algae densities increased with increasing fish feed dosages in moderate nutrients concentrations from fish feed 43 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, aquaculture activities not only stimulate algal growth but also affect phytoplankton communities 40,41 along with deteriorating water quality and adversely influencing human health aquaculture activities 42 . Wu et al 's results showed that the release of N and P from fish feed stimulated algae growth 43 . Algae densities increased with increasing fish feed dosages in moderate nutrients concentrations from fish feed 43 .…”
mentioning
confidence: 99%
“…Wu et al 's results showed that the release of N and P from fish feed stimulated algae growth 43 . Algae densities increased with increasing fish feed dosages in moderate nutrients concentrations from fish feed 43 . In Huang et al 's study, enclosures with fish feed have higher algae biomass than those without fish feed, and blue-green algae dominated phytoplankton communities in enclosures with fish feed 28 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Algae proliferation, a reduction in dissolved oxygen, reduced water transparency and their consequences for the phytoplankton and zooplankton communities are well-known consequences of aquaculture. Commonly, proliferation of undesirable algae (including Chlorophyceae) is caused by the amplification of nutrients associated with fish farming (Wu et al 2012). Here, we explore how tilapia cage farming influences phytoplankton community structure in eastern Brazil in the state of Espírito Santo.…”
Section: Introductionmentioning
confidence: 99%
“…When TP equals to 0.02mg/L, microalgae can grow well, but the concentration of phosphorus has no promotion to growth rate of algae when TP ≥ 0.2mg/L (Xu et al, 2006). Microalgae also select different formation of phosphorus, using different phosphors source to study, the result of research showed that dipotassium hydrogen phosphate is the biggest consumption for microalgae, which means this form of phosphorus is useful for microalgae growing (Wu et al, 2012).…”
Section: Nitrogen/phosphorus Nutrientmentioning
confidence: 99%